A comparative study on weld characteristics of AA5083-H112 to AA6061-T6 sheets produced by MFSC and FSSW processes. (August 2021) - Mehrez, S.; Paidar, M.; Cooke, K.; Vignesh, R.V.; Ojo, O.O.; Babaei, B.
Abstract: This study's objective was to conduct a comparative analysis and characterization of the microstructural evolution within the weld nugget for joints of AA5083-H112 and AA6061-T6 produced by friction stir spot welding (FSSW) and modified friction stir clinching (MFSC) processes. The mechanical performance of the welded joints was assessed in shear using a single lap joint. The microstructural study identified significant variation in joint microstructure and material flow due to the differences in the tool geometry and methodology used for the welding processes. The results show that the use of modified friction clinching process improves the welded joint by eliminating keyholes/hook defects leading to the formation of high-strength joints. Mechanical characterization of the welded joints indicated that the shear strength increased significantly from 78.69 MPa for the conventional FSSW to 131 MPa for the MFSC process. Highlights: AA5083-H112 and AA6061-T6 was successfully joined by MFSC process. MFSC process could remarkebly remove the keyhole defect. The addition of a second step for refilling the keyhole increased the mechanical strength of the welded joints.